2023
DOI: 10.1038/s41522-023-00381-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial mat compositions and localization patterns explain the virulence of black band disease in corals

Abstract: Black band disease (BBD) in corals is characterized by a distinctive, band-like microbial mat, which spreads across the tissues and often kills infected colonies. The microbial mat is dominated by cyanobacteria but also commonly contains sulfide-oxidizing bacteria (SOB), sulfate-reducing bacteria (SRB), and other microbes. The migration rate in BBD varies across different environmental conditions, including temperature, light, and pH. However, whether variations in the migration rates reflect differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…This sustains anoxic and sulfidic conditions and provides a niche for the consortium of BBD‐causing bacteria (Carlton & Richardson, 1995). A BBD migration rate across a coral surface is directly affected by initial bacterial abundance, which can speed up the disease process (Wada et al., 2023). For bacterial members involved in BBD, resistance to sulfide is key, and this allows them to survive within the BBD band niche space (Meyer et al., 2017).…”
Section: Resource Partitioning Structures Carbon Nitrogen and Sulfur ...mentioning
confidence: 99%
See 2 more Smart Citations
“…This sustains anoxic and sulfidic conditions and provides a niche for the consortium of BBD‐causing bacteria (Carlton & Richardson, 1995). A BBD migration rate across a coral surface is directly affected by initial bacterial abundance, which can speed up the disease process (Wada et al., 2023). For bacterial members involved in BBD, resistance to sulfide is key, and this allows them to survive within the BBD band niche space (Meyer et al., 2017).…”
Section: Resource Partitioning Structures Carbon Nitrogen and Sulfur ...mentioning
confidence: 99%
“…Mats form to create functionally similar communities across environments and are thus thought to form via deterministic processes (Stegen et al., 2012). Succession of early mat microbial members facilitates further colonization by other members by stabilizing areas of sediment through EPS, which is especially key in temperate marine habitats but present across ecosystems (Boomer et al., 2009; Gerbersdorf & Wieprecht, 2015; Wada et al., 2023). Succession is thus limited by recruitment and dispersal, filtering which members are able to colonize the existing mat (Tilman, 1994).…”
Section: Connecting Cycles: Succession and The Effects Of Disturbance...mentioning
confidence: 99%
See 1 more Smart Citation
“…TTX administration might enhance the proliferation of Arcobacter and other residential bacteria by inhibiting the growth of other bacteria. Previous research has suggested that the abundance of Arcobacter may be bene cial for the host rather than pathogenic host due to its metabolic capabilities for sulfur oxidation and carbon xation, as well as its ability to resist viruses in hag sh [17,47,122,68]. Previous study [112] reported that TTXfed sh exhibited the greatest growth at 8.5 ppt, followed by 34.0 ppt.…”
Section: In Uence Of Ttx On the Gut Microbiota Of Juvenile Takifugu R...mentioning
confidence: 99%
“…Additionally, it was found to be dominant in the ulcer mucus surfaces of Atlantic salmon, gut microbiota of hag sh, and giant abalone (Haliotis gigantea) [54,73,68,86]. Arcobacter species have a strong possibility of having the metabolic capacity for sulfur oxidation coupled with N-oxide reduction while xing carbon via the reverse TCA cycle [17,47,122]. Additionally, it is speculated that this species might possess the ability to resist viruses, potentially assisting in alleviating viral pressure [68].…”
Section: Gut Microbiota Of Juvenile Takifugu Rubripesmentioning
confidence: 99%